2010
DOI: 10.1590/s1516-35982010001000022
|View full text |Cite
|
Sign up to set email alerts
|

Balanço de nitrogênio, concentrações de ureia e síntese de proteína microbiana em caprinos alimentados com dietas contendo cana-de-açúcar tratada com óxido de cálcio

Abstract: RESUMO -Objetivou-se avaliar o efeito da hidrólise da cana-de-açúcar com óxido de cálcio (CaO) sobre o balanço de nitrogênio, as concentrações de ureia na urina e no plasma e a síntese na proteína microbiana em caprinos. Foram utilizados oito caprinos da raça Saanen, machos castrados, com peso corporal médio de 22,6 kg e 4 meses de idade, distribuídos em dois quadrados latinos 4 × 4, em quatro períodos experimentais de 14 dias. As rações, formuladas para ser isoproteicas, com 14% de proteína bruta (PB), foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…During ruminal fermentation, when the pool of ammonia exceeds the level of utilization by ruminal microorganisms, it is absorbed, reaching the liver through the enterohepatic circulation, where it is transformed into urea, which, together with the urea produced in the liver from amino acid metabolism, constitutes the majority of the plasma urea (ALVES et al, 2012). If urea is in excess in the blood circulation only part of it is recycled, via the saliva and the rumen wall, and goes back to the rumen, whereas the rest is excreted in the urine, causing endogenous losses of nitrogen (KOZLOSKI, 2002;CARVALHO et al, 2010). This was shown by Geron et al (2016) who, when evaluating the inclusion of SRU in sheep feed, observed a quadratic behavior with a point of maximum digestibility of 69.92% for DM and 63.55% for CP estimated for the levels of inclusion of 0.50% and 0.70% SRU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During ruminal fermentation, when the pool of ammonia exceeds the level of utilization by ruminal microorganisms, it is absorbed, reaching the liver through the enterohepatic circulation, where it is transformed into urea, which, together with the urea produced in the liver from amino acid metabolism, constitutes the majority of the plasma urea (ALVES et al, 2012). If urea is in excess in the blood circulation only part of it is recycled, via the saliva and the rumen wall, and goes back to the rumen, whereas the rest is excreted in the urine, causing endogenous losses of nitrogen (KOZLOSKI, 2002;CARVALHO et al, 2010). This was shown by Geron et al (2016) who, when evaluating the inclusion of SRU in sheep feed, observed a quadratic behavior with a point of maximum digestibility of 69.92% for DM and 63.55% for CP estimated for the levels of inclusion of 0.50% and 0.70% SRU.…”
Section: Resultsmentioning
confidence: 99%
“…circulation, where it is transformed into urea, which, together with the urea produced in the liver from amino acid metabolism, constitutes the majority of the plasma urea (ALVES et al, 2012). If urea is in excess in the blood circulation only part of it is recycled, via the saliva and the rumen wall, and goes back to the rumen, whereas the rest is excreted in the urine, causing endogenous losses of nitrogen (KOZLOSKI, 2002;CARVALHO et al, 2010). This was shown by Geron et al (2016) Nevertheless, the amount of UN is related to the content of CP in the diet, with increased excretion of urea via the urine when NI increases, as this results in higher production of urea in the liver, whereas a low NI leads to a decrease in the excretion of urea via the urine to maintain the plasma urea pool, under Nevertheless, the amount of UN is related to the content of CP in the diet, with increased excretion of urea via the urine when NI increases, as this results in higher production of urea in the liver, whereas a low NI leads to a decrease in the excretion of urea via the urine to maintain the plasma urea pool, under homeostatic physiological control (ZEOULA et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, excess N in the rumen is absorbed by the ruminal wall and enters the bloodstream, where it remains until eventually reaching the liver, where it is transformed into urea. This circulating urea can be partially recycled via saliva or returned to the rumen by transport facilitated by the ruminal wall, but when urea is in excess in the bloodstream, a part of it is excreted in the urine, resulting in endogenous N losses (KOZLOSKE, 2002;CARVALHO at al., 2010;GERON et al, 2015b). This process was not evident in the present study, most likely because most of the protein in DDGS is in the form of the B2 fraction (true protein of ruminal intermediary degradation) (GERON et al, 2017), which may have caused a small change in the rate of ruminal N release compared to diets containing a higher proportion of soybean meal, which corroborates with the results obtained for the UN of sheep fed DDGS.…”
Section: Variablesmentioning
confidence: 99%
“…Neste estudo, houve uma diminuição na concentração de glicose no plasma sanguíneo dos animais alimentados com semente de linhaça. Por esse motivo, provavelmente, as concentrações plasmáticas de ureia estão acima dos valores relatados na literatura (Carvalho et al, 2010) para a espécie caprina.…”
unclassified